Depression and Anxiety in Patients with Chronic Respiratory Diseases - Sharafkhaneh, Amir; Yohannes, Abebaw Mengistu; Hanania, Nicola A.; Kunik, Mark E. (Springer New York : Imprint: Springer, 2017)
In this unique title, the full range of chronic respiratory conditions and their association with psychiatric comorbidities are explored and targeted management options are outlined. Indeed recent studies indicate a far higher prevalence of depression and anxiety in patients afflicted with chronic respiratory conditions than in patients with other chronic disorders. Unlike other publications in the field of pulmonary disease, Depression and Anxiety in Patients with Chronic Respiratory Diseases details this significant correlation. The book is comprehensive in scope, covering such topics as depression and anxiety across the age spectrum, diagnostic tools for anxiety and depression, anxiety and depression in COPD patients, depression and anxiety in adult patients with asthma, and end-stage lung disease and lung transplantation, among others. In this novel work, the volume Editors enlist a team of renowned experts in the fields of respiratory and psychiatric disorders to combine a thorough synthesis of the literature with targeted, practical strategies for management. Depression and Anxiety in Patients with Chronic Respiratory Diseases is an invaluable resource for all clinicians who care for patients with chronic and advanced lung diseases.- Resumé vydavatel
Keywords: nemoci dýchacích cest; deprese; úzkost; chronicky nemocní; airways diseases; depression; anxiety; chronically ill; elektronické knihy; sborníky; electronic books; papers of several authors